Implementasi Pembelajaran Bahasa Arab Anak Usia Dini di RA Habibilla - Lubis, Hilda Zahra; Nasution, Annisa; Sunya, Astri Syakira; Latifah, Latifah (TSAQOFAH, 2025)
This study was conducted to find out about aerly childhood arabic language learning implementated by teachers at RA Habibilla. The data of this study were collected trought observation analysis and literature methods. The purpose of this study is about aerly childhood arabic language learning RA Habibilla, how teachers at RA Habibilla carry out early childhood arabic language learning using what methods and processes are in the teaching that is carried out.